2014
DOI: 10.1111/nph.12765
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of arbuscular mycorrhizal fungi: associations with grassland plant richness and biomass

Abstract: SummaryAlthough experiments show a positive association between vascular plant and arbuscular mycorrhizal fungal (AMF) species richness, evidence from natural ecosystems is scarce. Furthermore, there is little knowledge about how AMF richness varies with belowground plant richness and biomass.We examined relationships among AMF richness, above-and belowground plant richness, and plant root and shoot biomass in a native North American grassland. Root-colonizing AMF richness and belowground plant richness were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
205
4
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(245 citation statements)
references
References 94 publications
(156 reference statements)
17
205
4
8
Order By: Relevance
“…The results of the present study therefore indicate that there is a positive relationship between the above-ground plant diversity and the diversity and abundance of below-ground AMF. In support of the present findings, Hiiesalu et al (2014) had revealed that the AMF spore richness and abundance are positively correlated with plant species richness.…”
Section: Abundance Richness and Composition Of Amf Sporessupporting
confidence: 75%
“…The results of the present study therefore indicate that there is a positive relationship between the above-ground plant diversity and the diversity and abundance of below-ground AMF. In support of the present findings, Hiiesalu et al (2014) had revealed that the AMF spore richness and abundance are positively correlated with plant species richness.…”
Section: Abundance Richness and Composition Of Amf Sporessupporting
confidence: 75%
“…Previous study showed that relationships between plant biomass and soil fungal diversity varied with the seasonal dynamics of soil fungal community composition and of plant biomass production (Hiiesalu et al. 2014). In our study, the positive correlation between soil fungal richness and plant biomass in simple linear regression might be indirectly formed by soil gradient, because soil fungal richness and plant biomass are positively associated with soil gradient.…”
Section: Discussionmentioning
confidence: 99%
“…2011) and negative effects (Hiiesalu et al. 2014). Concurrently, many studies have also suggested that soil fungal diversity is strongly dependent on soil properties (Prevost‐Boure et al.…”
Section: Introductionmentioning
confidence: 99%
“…Such bottom-up relationships among diversity of food-web organisms occur both aboveground and belowground and are reflected along the trophic cascades (Scherber et al, 2010;Eisenhauer et al, 2013; but see Porazinska et al, 2003). Recent studies on natural grassland plants showed that plant species richness is positively correlated with that of several major fungal groups on a local scale (Hiiesalu et al, 2014;Pellissier et al, 2014). Richness of free-living protists, meiofauna and saprotrophic fungi may similarly benefit from specialization on different sources of food or substrate for decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all previous biodiversity studies have used traditional morphology-based identification methods to determine the richness of consumers (but see Hiiesalu et al, 2014;Pellissier et al, 2014). This approach requires substantial taxonomic expertise and long processing time given the large number of samples and individuals (Scherber et al, 2010).…”
Section: Introductionmentioning
confidence: 99%